Synthesis and characterization of carboxyl and acetal latexes by emulsion polymerization. Application to the production of latex-protein complexes for detecting chagas disease - Garcia, Valeria Soledad (2012)
Monodisperse polymer particles with carboxyl and acetal functionalities were synthesized through a two-step emulsion polymerization process. In the first step, latex particles were synthesized by batch emulsion polymerization of styrene (St); and in the second step, the functional monomers (methacrylic acid or acrolein diethyl acetal) were copolymerized with St onto the previously formed polystyrene particles. The synthesized “core-shell” latexes were used as support for their sensitization (by covalent coupling) with two antigenic recombinant proteins of Trypanosoma cruzi (RP1 and CP1). Polymer latexes and latex-protein complexes were characterized by measuring their colloidal stability, average particle size, shell thickness and protein thickness through conductimetric titration, dynamic light scattering, turbidimetry and scanning electron microscopy.